ANALISIS MAQĀṢID SYARĪ’AH TERHADAP PRAKTIK RENTENIR PADA MASYARAKAT PULAU KODINGARENG KOTA MAKASSAR - Hatta Rajasa, Muhammad; Raehana, Syarifa; Jamaluddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Kodingareng Island is an archipelagic area without formal financial institutions, while its residents, particularly fishermen, face unstable income and urgent financial needs. This condition has encouraged informal lending with high interest rates. This study aims to describe the mechanism of moneylending practices on Kodingareng Island and analyze their impacts through the framework of Maqāṣid al-Sharī‘ah. This qualitative field research used phenomenological and economic-sociological approaches. Data were obtained from 15 purposively selected informants through observation, in-depth interviews, and documentation, analyzed using the Miles and Huberman model, and validated through source and technique triangulation. The findings show that moneylending operates with interest rates of approximately 20–30 percent per month, accompanied by direct collection and additional charges for late payments. Residents continue to use these services because of limited financing alternatives and urgent needs. From the perspective of Maqāṣid al-Sharī‘ah, the practice generates mafsadah at the levels of daruriyyat, hajiyyat, and tahsiniyyat, affecting religion, life, intellect, lineage, and wealth, as well as livelihood and community economic resilience. The study concludes that moneylending is inconsistent with the objectives of Maqāṣid al-Sharī‘ah and requires fairer financing alternatives through strengthened Islamic financial inclusion.